Preparation Of Micro- And NanoSized Granulated Zn-Sb Compound Based On Powder Technology And Development Of Resistance Heating Method - Olimov Lutfiddin Omanovich; Akhmadaliev Utkirbek Akramjonovich (Genius Journals, 2023)
In this article, the technology of preparing Zn-Sb compound prepared in powder technology and the methods of obtaining thermoelectric material by heat joining with resistance means are analyzed. A mechanical method was used to prepare the semiconducting Zn-Sb compound, zinc-antimony particles were placed in a ceramic container and crushed to a nano-size, and placed in a special ceramic-shaped cylindrical tube, heated and thermally treated in several stages. One of the most important factors in obtaining the thermoelectric parameters of this compound is determined by the degree of fineness of the powder
Keywords: Powder technology; micro and nano size; thermoelectricity